Studies on Echocardiographic Assessment of Healthy Non Descript Dogs - Kunjadiya, Rajan J; Patel, Manish D; Parmar, Saurabh M; Mehta, Sudhir A; Vala, Jignesh A. (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Considering echocardiography as the most widely accepted non-invasive diagnostic tool for assessing cardiac anatomy and function  in small animals, present study was planned to assess echocardiographic parameters in dogs. Total 18 clinically healthy non-descript  dogs were subjected to 2-D and M-mode echocardiographic examinations. Dogs were categorized by gender, age and body weight to  assess their effects on various echocardiographic parameters. The mean LA, Ao, and LA/Ao ratio values were 1.70±0.04 cm, 1.72±0.05  cm, and 1.00±0.03, respectively, with non-significant group differences. However, the mean LA/Ao ratio was higher in dogs weighing  >20 kg (1.04±0.03) compared to those 3 years had significantly higher  mean values of EF (69.05±3.84%), FS (38.34±3.31%), and CO (1991.34±201.95 mL/min) compared to those
Keywords: 2-D and M-mode echocardiography; Non-descript dogs